Role of the subthalamic nucleus in perceiving and estimating the passage of time - Honma, Motoyasu; Sasaki, Fuyuko; Kamo, Hikaru; Nuermaimaiti, Maierdanjiang; Kujirai, Hitoshi; Atsumi, Takeshi; Umemura, Atsushi; Iwamuro, Hirokazu; Shimo, Yasushi; Oyama, Genko; Hattori, Nobutaka; Terao, Yasuo (Frontiers in Aging Neuroscience, 2023)
Sense of time (temporal sense) is believed to be processed by various brain regions in a complex manner, among which the basal ganglia, including the striatum and subthalamic nucleus (STN), play central roles. However, the precise mechanism for processing sense of time has not been clarified. To examine the role of the STN in temporal processing of the sense of time by directly manipulating STN function by switching a deep brain stimulation (DBS) device On/Off in 28 patients with Parkinson’s disease undergoing STN-DBS therapy. The test session was performed approximately 20 min after switching the DBS device from On to Off or from Off to On. Temporal sense processing was assessed in three different tasks (time reproduction, time production, and bisection). In the three temporal cognitive tasks, switching STN-DBS to Off caused shorter durations to be produced compared with the switching to the On condition in the time production task. In contrast, no effect of STN-DBS was observed in the time bisection or time reproduction tasks. These findings suggest that the STN is involved in the representation process of time duration and that the role of the STN in the sense of time may be limited to the exteriorization of memories formed by experience.